If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + -8) + -1ln(x + 9) = ln(x + -7) + -1ln(x + 1) Reorder the terms: ln(-8 + x) + -1ln(x + 9) = ln(x + -7) + -1ln(x + 1) (-8 * ln + x * ln) + -1ln(x + 9) = ln(x + -7) + -1ln(x + 1) (-8ln + lnx) + -1ln(x + 9) = ln(x + -7) + -1ln(x + 1) Reorder the terms: -8ln + lnx + -1ln(9 + x) = ln(x + -7) + -1ln(x + 1) -8ln + lnx + (9 * -1ln + x * -1ln) = ln(x + -7) + -1ln(x + 1) -8ln + lnx + (-9ln + -1lnx) = ln(x + -7) + -1ln(x + 1) Reorder the terms: -8ln + -9ln + lnx + -1lnx = ln(x + -7) + -1ln(x + 1) Combine like terms: -8ln + -9ln = -17ln -17ln + lnx + -1lnx = ln(x + -7) + -1ln(x + 1) Combine like terms: lnx + -1lnx = 0 -17ln + 0 = ln(x + -7) + -1ln(x + 1) -17ln = ln(x + -7) + -1ln(x + 1) Reorder the terms: -17ln = ln(-7 + x) + -1ln(x + 1) -17ln = (-7 * ln + x * ln) + -1ln(x + 1) -17ln = (-7ln + lnx) + -1ln(x + 1) Reorder the terms: -17ln = -7ln + lnx + -1ln(1 + x) -17ln = -7ln + lnx + (1 * -1ln + x * -1ln) -17ln = -7ln + lnx + (-1ln + -1lnx) Reorder the terms: -17ln = -7ln + -1ln + lnx + -1lnx Combine like terms: -7ln + -1ln = -8ln -17ln = -8ln + lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -17ln = -8ln + 0 -17ln = -8ln Solving -17ln = -8ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '8ln' to each side of the equation. -17ln + 8ln = -8ln + 8ln Combine like terms: -17ln + 8ln = -9ln -9ln = -8ln + 8ln Combine like terms: -8ln + 8ln = 0 -9ln = 0 Divide each side by '-9'. ln = 0 Simplifying ln = 0 The solution to this equation could not be determined.
| 150+(225*3.50)=2000 | | .25(j-8)=0.5j+2 | | 4(2a-4)=40 | | 4m-18m=112 | | 5-3x-21=4-2x-8 | | 10m-8(m+9)=88 | | y-1.34=9.89 | | 1-6x+5x=7 | | 7x-34x-48=0 | | 3n+15n=72 | | 2+(9-8)-34-6=22 | | X+(-17)+x+(-23)+2x=180 | | 3x+4(k-2)=4+x | | x^2-45=4050 | | (4x+5)+(5x-30)=180 | | 3x^3+3x^2=36 | | 5*2-13= | | 6(3y-12)=2(4y-5)+10y-8 | | x+0.32=0.45(x+9) | | 10x-2(x+3)=10 | | -3x+2=7x | | 7(4x-7)=2(14x+6) | | 2x-10=4x+8 | | 6x^2y+3x-9xy= | | 3.40x+2.80y=7.5 | | 9(2k+3)+2=11(k-1) | | 4-2.50-39.00=p | | 5times-8=12 | | 5y-9=21 | | 3.5f+10=-30 | | 6x+70=22 | | z=w*z^2-9y |